PENGUKURAN KEPUASAN NASABAH TERHADAP IMPLEMENTASI SYARIAH MARKETING PADA PT. BANK SYARIAH MANDIRI CABANG MALANG - Hasan, Irmayanti (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2017)
Competition is increasingly competitive in the development of Islamic bank in Indonesia and policy enforcement office channeling makes the atmosphere seizure of shari'ah loyalists consumers increasingly viscous. The phenomenon of this competition requires marketers to constantly innovate marketing strategies. One step to achieve this is through the implementation of sharia marketing.The approach used in this study is a survey approach and type of research is quantitative. This study used 16 items, then the sample is 80 customers.The results of this study are customers already feel very satisfied with the services of employees of PT. Bank Syariah Mandiri Malang Branch, but the performance of employees of PT. Bank Syariah Mandiri Malang Branch must still be improved. There are several strategies to increase customer satisfaction, there are some things that should be emphasized and some are already well do not need to be prioritized, but still need to be considered by PT. Bank Syariah Mandiri Malang Branch.